Lippincott's primary care rheumatology - Boulware, Dennis W.; Heudebert, Gustavo R. (Primary care series (Philadelphia, Pa.), 2012)
"This volume of Lippincott's Primary Care Series will help family practitioners, internists, nurse practitioners, and physician assistants understand, diagnose, and treat the most common rheumatologic problems seen in the primary care setting. Emphasis on day-to-day practical outpatient office practice distinguishes this from the many existing rheumatology textbooks and it contains numerous images to aid in diagnosis and treatment. Whenever possible, chapters follow a consistent format with headings of Clinical Presentation, Examination, Studies, Treatment, Clinical Course, and Conclusions and box elements such as Introductory Case, Clinical Points/Highlights, Patient Assessment, Not to Be Missed, and When to Refer. Key points are provided for those topics that don't fit this format"--Provided by publisher.